Structural Optimization Combined with Meshless Methods - 2D Applications - Gonçalves, Diogo Costa (2020)
Continuously, the industry seeks to reduce costs associated with the design and construction of structural materials. Today, structural optimization (or topologic optimization) is a large research area inside computational mechanics capable to reduce the amount of material used in the structure and, at the same time, assure its structural resistance and high performance. Thus, the development of new structural optimization algorithms and techniques will allow to produce structural elements using less material, leading to an overall cost reduction (design, production and use costs). Thus, the main objective of this dissertation is to implement and demonstrate the effectiveness of structural optimization in designing cost and energy efficient components. Although the Finite Element Method (FEM) isthe most used discretization technique within structural optimization, meshless methods have been extended to optimization algorithms in recent years. Meshless methods are advanced discretization techniques that allow to discretize the problem domain by only using an unstructured nodal distribution. In this work, the FEM and two Radial Point Interpolation (RPI) meshless methods are combined with an Evolutionary Structural Optimization (ESO) algorithm. The Radial Point Interpolation Method (RPIM) and the Natural Neighbour Radial Point Interpolation Method (NNRPIM) formulation are described with detail, as well as the fundamentals of mechanics of solids required to combine meshless methods with structural optimization algorithms. Also, a literature review on structural optimization algorithms and its coupling with meshless methods is given. Regarding the numerical simulation, the optimization algorithm is applied to benchmark problems, allowing to calibrate algorithm parameters, as well as evaluate mesh influence and computational time. Afterwards, the methodology is extended to several industrial applications. The implementation of the structural optimization algorithm allowed to design innovative structures with reduced volume. By implementing structural optimization and designing innovative structures based on algorithm solutions, this work demonstrates the diversity of applications and benefits of using structural optimization in the product design phase.